CONSTRUCTION OF SOCIAL SCIENCES AND HUMANITIES TOWARDS NUSANTARANOLOGY - Kamaruzzaman Bustamam Ahmad; Fitri Zulfidar Ibrahim (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2020)
This study is the first attempt to introduce the concept of Nusantaranology in Indonesia. Based on a bibliographic survey and the authors' experiences in research development, it appears that Indonesia has a very strong scientific foundation compared to other countries. Besides, the fact that the wealth of local treasures in Nusantara can be utilized as a first step to develop the scientific concept of Nusantaranology. In this study, the authors conducted a bibliographic survey on how the influence of Western social sciences and humanities on several studies or research in Indonesia. The authors argue that the influence of the Western scientific tradition needs to be re-examined in understanding the various local knowledge found in Nusantara. The authors also found that various research results from local researchers have shown that the products of knowledge in Nusantara are very profound if they are framed under a scientific umbrella, i.e Nusantaranology. Finally, this study is expected to be the first step for researchers in Indonesia to carry out various studies on local issues, while continuing to strengthen the philosophical foundations of science, to reinforce the concept of Nusantaranology or Indonesian Studies.